The influence of intelligence on the interest in becoming hybrid entrepreneurs among employees in Kupang city - Indawati J. Nino; Septia S. Dioh; Danny F. Wungubelen (Enrichment : Journal of Management, 2023)
The aim of this research is to investigate the mechanisms of the relationship between intelligence and the interest in entrepreneurship among permanent employees in the city of Kupang. There are many permanent employees who aspire to establish businesses without leaving their current jobs. These types of entrepreneurs are called hybrid entrepreneurs as they manage at least two professions simultaneously. The permanent employees from various government institutions in the city of Kupang were selected as the research sample as they represent a demographic group expected to have the ability and potential to become hybrid entrepreneurs. To achieve the research objectives, literature from the fields of entrepreneurship and psychology will be integrated to formulate the necessary hypotheses. The results show that intelligence influences intention to become hybrid entrepreneurs as mediated by fear of entrepreneurship